Nagmaalviering in die NG Kerk - tussen tradisie en vernuwing. Deel 3 - Burger, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
What became apparent in parts 1 and 2 of this series about the celebration of the Lord’s Supper in the Reformed tradition, the ecumenical world and the worldwide Reformed family, did not pass the General Synod of the Dutch Reformed Church unnoticed. Therefore this article will firstly look at some of the most important decisions pertaining to the Lord’s Supper that were made by the Dutch Reformed Church’s General Synod in the last decades. Secondly the similarity between the Liturgical Movement’s consensus regarding the Lord’s Supper, and the decisions of the General Synod as well as that which became apparent about the celebration of the Lord’s Supper in parts 1 and 2, will be highlighted. In spite of this consensus there is still a strange hesitation in local congregations towards the implementation of some of these decisions. The reasons for this state of affairs are explored, as well as the reasons why a more frequent celebration can be seen as an integral part of church and worship restoration. Lastly some practical guidelines that could assist in the implementation of a more frequent celebration are put on the table.